Ventriculotomy for the removal of a foreign body in a common myna (Acridotheres tristis): a case report - M. Champour; N. Ojrati (Veterinární Medicína, 2014)
A seven-month old common myna with a history of ingesting a wire was transferred to the Iranmehr companion animal clinic in Mashhad, Iran. The bird's symptoms included anorexia, retching, intermittent vomiting, a lack of vocalisation, fluffing, and nervousness lasting for two days. X-rays confirmed a radiopaque foreign body in the proventriculus. Initial attempts to remove the wire thorough the oral route were futile; however, surgical removal using ventriculotomy (ventral midline celiotomy) under general anaesthesia proved successful. Slight haemorrhaging occurred when the incision was made in the caudal aspect of the ventriculus, but overall, the procedure was performed with no serious complications. A follow-up after three month revealed no complications. Despite the negative views associated with this technique, our study shows that ventriculotomy can be recommended for the removal of ventricular and proventricular foreign bodies, at least in this species.